Detection of NO2 Down to One ppb Using Ion‐in‐Conjugation‐Inspired Polymer. Issue 2 (7th December 2018) - Zhou, Jin; Cheng, Xue‐Feng; Gao, Bi‐Jun; Yu, Chuang; He, Jing‐Hui; Xu, Qing‐Feng; Li, Hua; Li, Na‐Jun; Chen, Dong‐Yun; Lu, Jian‐Mei
Abstract: Nitrogen dioxide (NO2 ) emission has severe impact on human health and the ecological environment and effective monitoring of NO2 requires the detection limit (limit of detection) of several parts‐per‐billion (ppb). All organic semiconductor‐based NO2 sensors fail to reach such a level. In this work, using an ion‐in‐conjugation inspired‐polymer (poly(3, 3′‐diaminobenzidine‐squarine, noted as PDBS) as the sensory material, NO2 can be detected as low as 1 ppb, which is the lowest among all reported organic NO2 sensors. In addition, the sensor has high sensitivity, good reversibility, and long‐time stability with a period longer than 120 d. Theoretical calculations reveal that PDBS offers unreacted amine and zwitterionic groups, which can offer both the H‐bonding and ion‐dipole interaction to NO2 . The moderate binding energies (≈0.6 eV) offer high sensitivity, selectivity as well as good reversibility. The results demonstrate that the ion‐in‐conjugation can be employed to greatly improve sensitivity and selectivity in organic gas sensors by inducing both H‐bonding and ion‐dipole attraction. Abstract : An ion‐in‐conjugation inspired‐polymer (poly(3, 3′‐diaminobenzidine‐squarine)) is employed as in chemiresistor to detect NO2 as low as 1 ppb, which is the lowest among all reported organic NO2 sensors.